(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
Three species belonging to two genera of the family Euphorbiaceae are being reported here as new records for Bangladesh, viz., Cleidiocarpon laurinum Airy Shaw, Euphorbia pycnostegia Boiss. and Euphorbia repens K. Koch. The genus Cleidiocarpon Airy Shaw is also a new generic record for Bangladesh. One cultivated species, Acalypha wilkesiana Muell.-Arg., is reported as addition to the account of the Euphorbiaceae of Bangladesh. Description and photographs of these species are provided. Bangladesh J. Plant Taxon. 25(1): 93-99, 2018 (June)